Representasi Pelanggaran Etika Media Digital dalam Film Budi Pekerti Karya Wregas Bhanuteja - Siti Rabiah; Nurliah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This study aims to examine and explain the description of how violations of digital media ethics occur in the film Budi Pekert using Roland Barthes' semiotics. The film analyzed in this study is the film Budi Pekerti which was released in 2023. The research method used is qualitative which is descriptive interpretive with Barthes' semiotic technique which includes two levels of meaning, namely denotation and connotation, as well as myths contained in visual and verbal signs in the film being studied. The results of the study show that the film represents acts of violations of digital media ethics, namely the spread of fake news, the spread of personal information, mocking or mocking content and irresponsible actions through dialogue, dominant gestures, and the setting of the place that builds the action. At the myth level, the film Budi Pekerti depicts the conditions of Indonesian society in cyberspace. This film shows how important digital literacy is for each individual to create a social order that has a critical-creative mindset and perspective. This study concludes that films not only convey a story, but also transmit certain values ​​or cultures to the audience.